Imminence of trees: rhizomatic narrative encounters with indigenous and invasive socioecologies, water, food and livelihoods in Cape Town - O’Donovan, Grace Dalene (The University of Edinburgh, 2025)
The current crises of our time call for nuanced and novel ways of thinking about their interconnections, complexities, and contradictions to afford viable paths ‘through the wilderness’. In the Western Cape, experiences of inequality are intricately related to contextual political, economic, social and ecological oppressions that perpetuate South Africa’s ongoing historical apartheid and (post)colonial legacies, and which are increasingly exacerbated by climate change. This (post)critical, postqualitative research is transdisciplinary in nature and method, and brings together political ecology, posthumanism, indigeneity, and decoloniality, amongst other philosophies and cosmologies to address an entanglement of socioecological development challenges, while embracing a heartful, artsbased methodology of critical rhizomatic narrative. The inquiry beckons to an aesthetic, affective and ontological language-of-landscape in approaching the socioecological and climate challenges of the Anthropocene, against the violences of universalist and Euromodernist thought, frameworks, and research. The inquiry seeks to reveal how interrelated complexities and contradictions of a socioecological, material, spatial, cosmological, economic and political nature play out in the ‘everyday/night lives’ of residents. These stories speak to experiences of crisis-and-resistance in the Anthropocene in relation to invasive species, water, food, medicinal plants, conservation, informal economies, education, and urban gardening. The inquiry engages themes of forests, trees, the ocean, and indigenous southern African storytelling to find rhizomatic pathways to the possibilities of justice, radical hope, and a viable future for all ecological life.
The imminence of trees: rhizomatic narrative encounters with indigenous and invasive socioecologies, water, food and livelihoods in Cape Town
Keywords: climate change; posthumanism; invasive socioecologies; indigenous socioecologies; politics of water; politics of food; arts based research; critical rhizomatic narrative; decoloniality; climate justice; international development; political ecology; South Africa; Cape Town; invasive species; biodiversity; emotional geographies; spatial geographies; informal economies; storytelling; transdisciplinary research; narrative inquiry; translanguaging